Preparation of activated carbons from coffee husks utilizing FeCl3 and ZnCl2 as activating agents - Oliveira, Luiz C. A. (2009)
Ferric chloride was used as a new activating agent, to obtain activated carbons (AC) from agro industrial waste (coffee husks). This material was compared with two samples from the same raw material: one of them activated by using the classical activating agent, zinc chloride, and the other, activated with a mixture of the two mentioned activating agents in the same mass proportion. The carbonaceous materials obtained after the activation process showed high specific surface areas (BET), with values higher than 900 m2 g-1. It is interesting to observe that the activation with FeCl3 produces smaller pores compared to the activation with ZnCl2. An important fact to emphasize in the use of FeCl3 as activating agent is the activation temperature at 280 °C, which is clearly below to the temperature commonly employed for chemical or physical activation, as described in the bibliography. All the studied materials showed different behaviors in the adsorption of methylene blue dye and phenol from aqueous solutions.